Pembangunan Ekonomi Islami Menurut Fahim Khan Dan Umer Chapra: Sebuah Kajian Komparatif - Wiwin Fitriyah (Universitas Islam Lamongan, 2019)
Every economic system in the world is the ultimate goal of creating a prosperous, just and equitable life. The effort to achieve this goal is economic development. The highest achievement in the Islamic economic system is the fulfillment of fala>h, while fala>h can be achieved by fulfilling the concept of maqa>sid shari>ah, meaning say, preservation of beliefs, soul, spirit, heredity and property. Some theories about economic development strategies are often formulated by conventional economists framed by the ideology of capitalism and socialism. But the idea can not be separated from the critical projector. In the ranks of contemporary Islamic economic thinkers, criticism of Western development strategies is accompanied by an alternative offer. The object of this research is the reflection of Fahim Khan and Umer Chapra on economic development. This research uses qualitative method, with comparative descriptive analysis technique. From the existing data, the author tries to describe the two objects of research and analyze it, then compare the results of two research objects. After knowing the location of equations and differences, the authors analyze the factors that underlie it. The results show that there are similarities with the problems faced by developing countries. This is the high rate of unemployment or overwork. Fahim Khan also proposes economic development strategies for surplus countries by opening up and animating entrepreneurship as well as institutional support based on a partnership with the system (profit and loss sharing). If the theory of Chapra has nothing to do with the strategy it proposes, it is only the result of the criticism of capitalist and socialist existence that has failed to overcome the problems facing the developing countries. Its strategy focuses on four important elements: moral filters, correct motivation, socio-economic restructuring and the role of the state. There are 5 characteristics that influence the factors that cause the differences and similarities between Fahim Khan's and Umer Chapra's theories on economic development: action, context, history, power, and ideology. Keywords: Fahim Khan's Theory, Umer Chapra's Thoughts, Islamic Economic Development